2012
DOI: 10.4103/0975-7406.100302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C and hepatitis B virus infection(s) in patients with oral lichen planus

Abstract: Aim:The aim of this study was to determine the prevalence of hepatitis B virus and hepatitis C virus (HCV) infections in patients with oral lichen planus (OLP) and to compare it with that of general population.Materials and Methods:A total of 60 patients were included in the study. Patients were selected from the outpatient department of Rama Dental College Research Centre, Kanpur, Uttar Pradesh. Thirty patients with OLP were included in Group 1. Thirty age- and sex-matched healthy patients with no history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…A study performed in Italian patients with OLP and HCV showed a statistically significantly higher frequency of human leukocyte antigen (HLA)‐DR6 in HCV patients compared with patients without HCV infection, suggesting that HCV‐positive patients with HLA‐DR6 are more prone to develop OLP lesions . It is estimated that patients with hepatitis C are twice as likely to develop LP than the general population . Figueiredo et al .…”
Section: Etiologymentioning
confidence: 99%
“…A study performed in Italian patients with OLP and HCV showed a statistically significantly higher frequency of human leukocyte antigen (HLA)‐DR6 in HCV patients compared with patients without HCV infection, suggesting that HCV‐positive patients with HLA‐DR6 are more prone to develop OLP lesions . It is estimated that patients with hepatitis C are twice as likely to develop LP than the general population . Figueiredo et al .…”
Section: Etiologymentioning
confidence: 99%
“…Exacerbation of lichen planus was described earlier in patients treated with recombinant interferon alfa-2a [16,17] and interferon alfa-2b [18] but also in those treated with pegylated interferon alfa [19]. It must be emphasized that one recent study showed no association of HCV and lichen planus in a series of 60 patients [20]. The recent introduction of direct-acting antivirals, telaprevir and boceprevir, as a part of a triple combination regimen has significantly widened the spectrum of the so-called uniform entity of dermatitis associated with peginterferon/ribavirin only [21].…”
Section: Discussionmentioning
confidence: 98%
“…16,17 No concrete association between LP and HCV was detected in India. 8,9,13,18 Hepatitis B virus (HBV) has also been shown to have a causal association in LP cases. 1,19,20 Other viruses which have been implicated in the pathogenesis of LP include human herpesvirus-6 and human herpesvirus-7 and varicella zoster virus.…”
Section: Various Studies Editorials and Meta-analyses Have Demonstramentioning
confidence: 99%
“…[2][3][4][5][6] Many reports have shown contrasting results to this which has been attributed to various factors ranging from genetics to regional differences. [7][8][9][10] Another reason for these contrasting results is that many have included clinically diagnosed cases of lichen planus without histological confirmation which may lead to erroneous results as we know many lichenoid disorders can mimic lichen planus. Lichen planus is still quoted when chapters are written about the possible association with Hepatitis B and C virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation